The characteristics of acoustic wave propagation in rotating solid-state media - Durukan, Yasemin; Lutovinov, Andrey I.; Peregudov, Aleksander N.; Popkova, Ekaterina S.; Shevelko, Michail M. (2018 IEEE Conference of Russian Young Researchers in Electrical and Electronic Engineering (EIConRus), 2018)
The results of theoretical and experimental researches of acoustic wave propagation into rotating solid-state media are presented. The influence of various rotation directions on wave characteristics is considered. The wave parameters, dependent from rotation velocity, which can be used as an informative signal for angular velocity sensors, are found. Some fundamentally new concepts for motion sensor design, based on bulk acoustic waves, are offered.